The Distinctive Feature Analysis of the Figures in the Novel Singgasana Tak Bertuah by Mira Pasolong and the Novel Di Bawah Bayang-Bayang Ode by Sumiman Udu - La Alu; Hijriana Nur (Journal of Indonesian Language Education and Literary, 2017)
The distingtive element between the novel Singgasana Tak Bertuah and the novel Di Bawah Bayang-Bayang Ode can be seen in the following events. Novel Singgasana Tak Bertuah begins with the story of the figure Rafiah from the social stratum of ordinary society beloved by Muchlis of the noble descent (blue blood). Novel Di Bawah Bayang-Bayang Ode begins with the story of a man named Imam of the social stratum of ordinary people who tried to love Amalia Ode from the noble descent (blue blood). The second event in the novel of the Singgasana Tak Bertuah of romance between Rafiah and Muchlis gets rejection from Muchlis's mother because Rafiah is not from the noble class (blue blood), whereas in the novel Di Bawah Bayang-Bayang Ode which is the romance between Imam and Amalia Ode gets rejected by Amalia Ode's mother because Imam is not a noble descendant (blue blood). The third event in the novel of Singgasana Tak Bertuah, figure Rafiah is a formal education to the second degree (master's degree), whereas the figure of Amalia in the novel Di Bawah Bayang-Bayang Ode is formal education only to the high school level. The fourth event of Muchlis's character in the novel of Singgasana Tak Bertuah is formal education only up to the level of one degree (S1), while in the novel Di Bawah Bayang-Bayang Ode takes the world of formal education to the Doctoral degree (S3).